1994
DOI: 10.1093/cercor/4.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Synaptogenesis in the Prefrontal Cortex of Rhesus Monkeys

Abstract: Since the turn of the century, the prefrontal association areas of the cerebral cortex have been thought to be among the last regions of the cortical mantle to develop. We have examined the course of synaptogenesis in the macaque prefrontal cortex by quantitative electron microscopic analysis in 25 rhesus monkeys ranging in age from embryonic day 47 (E47) to 20 years of age. A series of overlapping electron micrographs spanning the whole cortical thickness in each animal provided data on the number, the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
420
1
7

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(458 citation statements)
references
References 0 publications
30
420
1
7
Order By: Relevance
“…At the macroscropic level, studies of both monkeys and humans have documented widespread exuberant production of connections throughout all brain regions in the early postnatal period (Zecevic et al 1989;Bourgeois and Rakic 1993;Bourgeois et al 1994;Huttenlocher and de Courten 1987;Huttenlocher and Dabholkar 1997). Across brain areas, the number of synapses plateaus at levels nearly twice as high as those observed in the adult brain, and then slowly declines to normal adult levels across the period of childhood and adolescence (see Fig.…”
Section: Synaptic Exuberance and Pruningmentioning
confidence: 99%
“…At the macroscropic level, studies of both monkeys and humans have documented widespread exuberant production of connections throughout all brain regions in the early postnatal period (Zecevic et al 1989;Bourgeois and Rakic 1993;Bourgeois et al 1994;Huttenlocher and de Courten 1987;Huttenlocher and Dabholkar 1997). Across brain areas, the number of synapses plateaus at levels nearly twice as high as those observed in the adult brain, and then slowly declines to normal adult levels across the period of childhood and adolescence (see Fig.…”
Section: Synaptic Exuberance and Pruningmentioning
confidence: 99%
“…Towards the end of gestation, neuronal circuits within the cortical plate gradually develop, as revealed by the significant increase in synaptogenesis 31 and accelerated maturation of cortical plate neurons. 4 However, these changes are probably not caused just by the relocation of synaptogenesis from the subplate zone into the cortical plate, but also by the functional change of γ-aminobutyric acid (GABA) from excitatory to inhibitory.…”
Section: Comparison Of Mri and Histological Findingsmentioning
confidence: 99%
“…These late developmental refinements coincide with the ability to perform higher cognitive tasks (Fuster 2002) and the coming "on line" of the frontal cortex (Goldman-Rakic 1987). Taken together, these studies suggest that cortical circuitry is being refined late in childhood and early adolescence to allow for the efficient processing necessary for adult cognition.Previous postmortem studies have shown that synaptic density in cortical association areas increases after birth, peaking in early childhood and then exhibits late developmental reductions, or "pruning" in the human (Huttenlocher 1979;Huttenlocher and Dabholkar 1997) and the non-human primate (Rakic et al 1986;Bourgeois et al 1994), reaching adult levels in late adolescence or early adulthood. Similarly, the density of dendritic spines on cortical pyramidal neurons also declines by as much as 50% during this developmental period in non-human primates (Anderson et al 1995).…”
mentioning
confidence: 99%
“…Accordingly, it is the synapses onto spines that have been shown to be selectively eliminated after birth (Zecevic et al 1989). In contrast, axodendritic synapse density does not change appreciably after birth and does not show this same dynamic pattern of development (Bourgeois et al 1994).Previous studies in the non-human primate suggest that synapses develop at the same rate in different cortical layers (Rakic et al 1986;Bourgeois et al 1994). In contrast, studies by Huttenlocher and Dabholkar (Huttenlocher and Dabholkar 1997) suggest that synaptogenesis occurs later in layers 2 and 3 than in layers 4-6 in the middle frontal gyrus of the human.…”
mentioning
confidence: 99%